The resource curse in renewable energy: A framework for risk assessment - Leonard, A; Ahsan, A; Charbonnier, F; Hirmer, S (Elsevier, 2022)
Renewable energy development can enable climate-compatible growth in low- and middle-income countries, particularly given the substantial opportunities for energy export to high-income countries seeking to decarbonise their energy systems. However, this also comes with significant risks, including the potential to trigger a resource curse of adverse social, environmental, and economic effects resulting in paradoxically slowed growth. Here, we propose a novel framework to assess potential risks associated with renewable energy development in low- and middle-income countries rooted in the resource curse literature. Eighteen symptoms of the resource curse are evaluated in terms of relevance to renewable energy, and their potential risks and benefits during renewable energy development are established. We find that context-specific factors are key in determining whether resource developments will provoke adverse impacts or positive opportunities; so, preemptive context-specific risk assessment is needed to implement prevention and mitigation strategies. For example, while fossil fuel development has been seen in some circumstances to increase dependence on external capital and technology, where adequate education and financing strategies are implemented, it can instead enhance autonomy and development. Similar risks can apply to renewable energy development, and must be evaluated. The proposed resource curse risk assessment framework can be applied to individual contexts to help countries, companies, sectors, or projects maximise the positive outcomes of renewable energy development and avoid a renewable energy resource curse.